2019
DOI: 10.26434/chemrxiv.10001924
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Process Description of an Unconventional Biofilm Formation by Bacterial Cells Autoagglutinating Through Sticky, Long, and Peritrichate Nanofibers

Abstract: <p></p><p>Biofilms are used in environmental biotechnologies including waste treatment and environmentally friendly chemical production. Understanding the mechanisms of biofilm formation is essential to control microbial behavior and improve environmental biotechnologies. <i>Acinetobacter </i>sp. Tol 5 autoagglutinate through the interaction of the long, peritrichate nanofiber protein AtaA, a trimeric autotransporter adhesin. Using AtaA, without cell growth or the production of ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…However, the current result demonstrated that a single Tol 5 cell itself has the ability to very strongly adhere to a surface through the quick interaction of AtaA with the surface. It is considered that the strong initial attachment capacity of Tol 5 cells using AtaA gives this bacterium the property of forming a strongly attached biofilm without the secretion of EPS, as shown previously [35].…”
Section: Adhesion Force Mapping Of a Single Cell Of Various Bactermentioning
confidence: 73%
See 3 more Smart Citations
“…However, the current result demonstrated that a single Tol 5 cell itself has the ability to very strongly adhere to a surface through the quick interaction of AtaA with the surface. It is considered that the strong initial attachment capacity of Tol 5 cells using AtaA gives this bacterium the property of forming a strongly attached biofilm without the secretion of EPS, as shown previously [35].…”
Section: Adhesion Force Mapping Of a Single Cell Of Various Bactermentioning
confidence: 73%
“…AtaA on the cell surface was immune-stained with anti-AtaA699-1014 antiserum and Alexa Fluor 488-conjugated antirabbit antibody (Cell Signaling Technology, Danvers, MA, USA) and detected using a flow cytometry system (FACS Canto II; Becton, Dickinson and company). Recently, we showed that autoagglutination through AtaA significantly contributes to biofilm formation of Tol 5 cells by triggering the formation of the biofilm [35,36].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we showed that autoagglutination through AtaA significantly contributes to biofilm formation of Tol 5 cells by triggering the formation of the biofilm [35,36].…”
Section: Adhesion Force Mapping Of a Single Cell Of Various Bactermentioning
confidence: 99%